A qualitative study of young peoples’ thoughts and attitudes to follow a more plant-based diet - McInnes, Catherine; Carstairs, Sharon A.; Cecil, Joanne E. (Frontiers in Psychology, 2023)
Plant-based diets (PBDs) refer to dietary habits that reduce the consumption of animal-based products and increase the consumption of nutritionally rich plant foods. PBD's have been shown to provide significant health benefits, such as reducing obesity and improving psychological wellbeing, and are environmentally friendly. However, few studies have investigated factors that influence young people's thoughts and attitudes towards following a PBD in western societies, particularly in the United Kingdom. Understanding these factors may benefit public health interventions that encourage the consumption of more fruit and vegetables. The aim of this study was to explore the factors that affect young people's intentions towards following a PBD. Twenty-one young people (18-24 years) participated in this qualitative study. Participants were asked about their views of PBDs in a semistructured interview. Thematic analysis was utilised to explore views and the barriers and facilitators to following a PBD. The Theory of Planned Behaviour (TPB) was used as a framework to organise the findings. Within attitudes, the sub-themes identified were an awareness of a healthy diet, environmental concerns, health concerns and distrust, perceptions of PBDs and associated stereotypes, perceived restriction and lack of enjoyment, and need for education. Within subjective norms, the sub-themes identified were cultural and familial norms, peer influence, and exposure through social media. Within perceived behavioural control (PBC), the subthemes identified were a lack of independence and parental control, lack of knowledge and perceived difficulty, lack of inclusiveness and accessibility, and inconvenience. Overall, the findings suggest that increased provision of education and knowledge about PBDs to young people, and widening access to PBDs, could encourage and help improve their understanding and intention to follow this dietary style. Tailored health promotion strategies, which also consider additional barriers ATTITUDES TOWARDS PLANT-BASED DIETS 2 and facilitators found within this study, could motivate young people to consume a more PBD.